Studying the possibility of using dam sediment to improve some properties of sandy soil - هديل معمار; منى علي بركات; عزيز أسعد; غسان ناعسة (Latakia University Journal -Biological Sciences Series, 2023)
The experiment was carried out at the Snubar Jableh Agricultural Research Station in Lattakia during the 2021 agricultural season, according to a randomized complete block design (RCBD) with three replications for each treatment. The research aimed to study the effect of adding dam silt on some properties of sandy soil. The addition of sediments at levels (S4,S3,S2,S1) led to a significant improvement in the studied physical properties of the soil, where the fourth level S4 had the greatest impact on that, as the volume distribution of soil particles gave an increase in the clay percentage of 253,33% compared to the control, While the value of the hydraulic conductivity at the same level was 88% compared to the control, as for the volume distribution of soil pores, the percentage increase for the fourth level was 52.18% compared to the control, while the value of the average diameter of the soil aggregates was 2.1 mm, for the fourth level compared to the control, and this indicates On the high degree of soil stability factor, it was also observed that the moisture content at the field capacity of the fourth level increased to 136% compared to the control, while the increase in the percentage of available water amounted to 90.98%, Based on the above, it can be suggested to add dam silt to improve the physical properties of sandy soil.